ANALISIS KEBUTUHAN ALAT DAN MESIN PERTANIAN UNTUK MENDUKUNG INDEKS PERTANAMAN 200 DI LAHAN RAWA LEBAK - Fidel Harmanda Prima; Rizky Tirta Adhiguna; Edward Saleh; Hersyamsi hersyamsi; Endo Argo Kuncoro (Jurnal Technopreneur (JTech), 2023)
This study aims to analyze the need for agricultural machinery to support a cropping index of 200 in swampy land. This research was conducted in August 2021 in Muara Abab Village, Rantau Bayur District, Banyuasin Regency, South Sumatra Province. This study used a descriptive-tabular method, while collecting primary data using survey techniques and semi-structured interviews. Secondary data collection was obtained through a literature study conducted to collect data on institutions and policies supporting the development of agricultural tools and machinery. The data obtained was processed descriptively and analyzed to see farmers income and the data is presented in the form of tabulations. The results showed that the total income of lebak swamp farmers was IDR 8,963,625.00/ha/year. To support the activities of the index cropping 200, it is necessary to add additional agricultural equipment such as 5 units of 2-wheeled tractors, 1 unit of 4-wheeled tractors, 9 units of water pumps, 5 units of combine harvesters, 14 units of threshers and dryer as much as 2 units. Keywords: agricultural machinery, swampy land, cropping index 200, productivity